The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13018-016-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk of impaired bone apposition to titanium screws with the use of fibroblast growth factor-2−apatite composite layer coating

Abstract: BackgroundLoosening of screws is a common problem in orthopedic and maxillofacial surgery. Modifying the implant surface to improve the mechanical strength of screws has been tried and reported. We developed screws coated with fibroblast growth factor-2 (FGF-2)−apatite composite layers. We then showed, in a percutaneous external fixation model, that this composite layer had the ability to hold and release FGF-2 slowly, thereby reducing the risk of pin tract infection of the percutaneous external fixation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Their analysis for 5-year overall survival included eight studies and concluded that patients receiving LSS had significantly better results than those receiving amputation [28] . On the other hand, the meta-analysis from He et al that included ten studies supported that patients managed either with LSS or amputation had similar 5-year survival [11] . Excluding three studies that caused heterogeneity and whose subjects were Asians; however, they found that the 5-year overall survival rate was higher in patients treated with LSS than those treated with amputation [11] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Their analysis for 5-year overall survival included eight studies and concluded that patients receiving LSS had significantly better results than those receiving amputation [28] . On the other hand, the meta-analysis from He et al that included ten studies supported that patients managed either with LSS or amputation had similar 5-year survival [11] . Excluding three studies that caused heterogeneity and whose subjects were Asians; however, they found that the 5-year overall survival rate was higher in patients treated with LSS than those treated with amputation [11] .…”
Section: Discussionmentioning
confidence: 97%
“…There are two main surgical techniques: limb salvage surgery (LSS) and amputation [11] . Limb salvage techniques aim to widely excise of the tumor at the margins of healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the fundamental reason for the use of this smaller amount of injected SVFs in clinical application is likely the inability of investigators to isolate large number of cells from adipose tissue collected from their patients. Most of the stem cell studies also used this general number range of stem cells, likely due to high costs and cumbersome technique necessary to provide large number of stem cells [ 34 ]. One exception was particular autologous human adipose-derived MSCs (ADMSCs) study by Ra et al in spinal cord injury (SCI) patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first whole knee joint FE modelling study, where the subject number is this large. In most of the previous knee joint finite element studies, the subject number was restricted to one or two 47 – 49 . On the other hand, since our inclusion criteria were tight, there were only 7 suitable subjects for KL3 group in OAI database.…”
Section: Discussionmentioning
confidence: 99%